“A letra é a mesma, mas a cultura é diferente”: a escola dos Tupinambá de Olivença - Santana, José Valdir Jesus de (Universidade Federal de São Carlos, 2015)
In this dissertation, we aim at understanding how and why the Tupinambá from Olivença make school and how this school has become central in the production of strong people in the culture, update and production of kinship, being a relative and being in the culture, as they usually assert. Thus, we were interested in thinking how being in the culture and becoming strong in the culture are being produced from the school and the relationships enabled and coordinated by it, both internally and externally, in the movement that multiplies the school on the Indigenous territory, especially by the reclaimed areas, in order to understand this multiplier effect that relates to politics among the Tupinambá. This happens because, among these Indigenous people, making school, playing politics, claiming, producing reclaimed schools, being in the culture, producing culture, all these update and produce identity, kinship, being a relative and being smart people.
Keywords: Cultura; Escola Tupinambá; Parentesco; Estar na cultura; Culture; Tupinambá school; kinship; Living culture; CIENCIAS HUMANAS::ANTROPOLOGIA